PENGELOLAAN MEDIA SOSIAL DI LINGKUNGAN DINAS SOSIAL KABUPATEN BANGKALAN - BUYUNG PAMBUDI (JA (Jurnal Abdiku) : Jurnal Pengabdian Kepada Masyarakat, 2024)
Social media is often described as a communication tool that can trigger new ways of communicating through intermediaries. Social media is now an important means of delivering messages, exchanging messages, and searching for information needed online. In line with the increase in internet users in Indonesia, the number of social media users has also increased every year. So, it cannot be denied that social media is a place where an abundance of information is available today. However, the abundance of information is not necessarily all reliable information. Therefore, knowledge and skills are needed for trusted information owners to participate in using social media as a means of disseminating credible information, especially in the health sector. Training for all heads of Puskesmas in Bangkalan can be a means of gaining knowledge and skills in the use of social media in disseminating information about health.